The Role of Extracts of Edible Parts and Production Wastes of Globe Artichoke (Cynara cardunculus L. var. scolymus (L.)) in Counteracting Oxidative Stress - Valentina Laghezza Masci; Irene Mezzani; Enrica Alicandri; William Tomassi; Anna Rita Paolacci; Stefano Covino; Vittorio Vinciguerra; Elisabetta Catalani; Davide Cervia; Mario Ciaffi; Stefania Garzoli; Elisa Ovidi (Antioxidants)
In addition to the immature edible flower heads, the cultivation of globe artichoke (Cynara cardunculus L. var. scolymus (L.) Fiori) generates substantial quantities of by-products, including leaves, stems, and roots, which constitute potential sources of bioactive compounds and prebiotic dietary fiber. Preserving agricultural biodiversity and promoting socioeconomic development are essential for enhancing domestic production and fostering innovation. In the search for new biomolecules with antioxidant properties, this research focused on a globe artichoke landrace at risk of genetic erosion, still cultivated in the northern part of the Lazio region, known as the “Carciofo Ortano”. To investigate the antioxidant properties of various globe artichoke tissues from the “Carciofo Ortano” landrace, methanolic extracts were prepared from the immature main and secondary flower heads, stems, and leaves of representative genotypes of this landrace. Additionally, extracts were obtained from the same tissues of four landraces/clones included in the varietal platform of the PGI “Carciofo Romanesco del Lazio”, which served as reference genotypes: Campagnano, Castellammare, C3, and Grato 1. The antioxidant properties of these extracts were assessed using FRAP, ABTS, DPPH assays, and total phenolic content (TPC). The stem and secondary flower head extracts of two representative “Carciofo Ortano” genotypes and the Grato 1 clone, which have higher phenolic content, demonstrated the highest antioxidant activity. These extracts were therefore studied for their chemical profile using HPLC-DAD and SPME-GC/MS analysis. Additionally, the same extracts were investigated in vitro for their antioxidant capacity in differentiated SH-SY5Y cells, assessing their effects on ROS levels and the restoration of GSH levels. Furthermore, the in vivo beneficial effects of counteracting oxidative stress were evaluated in high sucrose-fed Drosophila melanogaster, as oxidative stress is a typical hallmark of hyperglycemic status. Overall, the results indicated that the edible immature inflorescences of the “Carciofo Ortano” landrace, along with the byproducts of its cultivation, are sources of raw materials containing biomolecules whose properties can be exploited for further applications in the pharmaceutical and medical sectors.